ANALISIS TINGKAT APRESIASI SENI RUPA SISWA DALAM MATA PELAJARAN SENI BUDAYA SUB BIDANG STUDI SENI RUPA DI SEKOLAH MENENGAH PERTAMA NEGERI 34 PADANG - Ulfia Sari, Dr. Ramalis Hakim, N.Pd., Drs. Yusron Wikarya, M.Pd. (Serupa The Journal of Art Education, 2018)
This study aims to analyze how the level of appreciation of students' fine arts in the subject of cultural arts sub-section of Fine Arts Study in SMP N 34 Padang. Researchers use observation, documentation and interview methods to analyze it. The results showed that the appreciation of students at the level of enjoying, liking and reacting had good results, while at the productive level it was still not good. In the Student Fine Arts Appreciation Process of SMP N 34 Padang, judging from the process of observation, introduction, the process of living and the process of evaluating the works of art during appreciation activities, it was known that students were able to appreciate well.Key Words: Fine Art Appreciation Level